AntagomiR-19a Induced Better Responsiveness to Bortezomib in Myeloma Cell Lines - Azam Kazemi (Royan Institute (ACECR), Tehran, 2021)
Objective: Multiple myeloma (MM) is the clonal proliferation of neoplastic plasma cells in the bone marrow. Although bortezomib (BTZ) is a crucial drug for the treatment of MM, drug resistance is a major problem. OncomiR-19a plays an oncogenic role in many cancers, including MM; however, the function of miR-19a in the pathogenesis of MM and drug resistance has not been completely identified. The present research aims to investigate the inhibition of miR-19a by an antagomir to determine BTZ responsiveness, and determine if miR-19a can be a prognostic biomarker for MM. Materials and Methods: In this experimental study, viability and apoptosis of myeloma cells were analysed by the colorimetric 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-Diphenyltetrazolium Bromide (MTT) and Annexin V/propidium iodide (PI) flow cytometry assays. Quantitative real-time polymerase chain reaction (qRT-PCR) was implemented to evaluate the expression levels of miR-19a, its targets SOCS3, STAT3, B-cell lymphoma 2 (BCL-2), PTEN and CDKN1A (antiapoptotic and cell cycle related genes) at the mRNA level. Results: miR-19a was downregulated and exacerbated in transfected cells treated with BTZ. The rate of apoptosis in the myeloma cells after BTZ treatment considerably increased, which indicated an increase in the mRNA of SOCS3, PTEN, BCL-2, and CDKN1. A decrease in STAT3 was also observed. Conclusion: OncomiR-19a, as a biomarker, may induce better responsiveness to BTZ in myeloma cell lines through its targets SOCS3, STAT3 and PTEN. In the future, this biomarker may provide new therapeutic targets for MM.